Multilocular Unicystic Ameloblastoma of Mandible - Manas Bajpai; Deshant Agarwal; Anindya Bhalla; Malay Kumar; Rakesh Garg; Manish Kumar (Case Reports in Dentistry)
Introduction. We report a rare case of unicystic ameloblastoma (UA) of mandible which showed multilocular radiolucency on the left side of mandible on radiographic examination which is very unusual, and the majority of the cases of UAs till date has been reported of unilocular radiolucency. On histopathological examination, an odontogenic cystic lining that proliferates that intraluminally resembling ameloblastomatous epithelium was observed, leading to a definitive diagnosis of unicystic ameloblastoma. Case Presentation. A 42-year-old male patient presented with a swelling on the left side of the mandible extending from 33 to 36. Radiographically, it showed a multilocular radiolucent lesion resembling odontogenic cyst; however, the final diagnosis was made on histopathological ground with the inclusion of radiological and clinical features. Conclusion. It can be concluded that at present, histopathologic examination is the most sensitive tool for differentiating between odontogenic cysts and UAs. However, both clinical and radiologic findings share equal contribution to the final diagnosis.